Optimization of functioning national evaluation of the technical condition of transport vehicles - Шаша, Игорь Константинович; Маренко, Геннадий Николаевич (Eastern-European Journal of Enterprise Technologies, 2009)
The paper deals with optimizing the operation of the national system of evaluation of the technical condition of transport vehicles by creating a high-performance auto-service regional centers. We propose a systematic approach to the development of models of formation of technical reliability of transport vehicles, based on the prediction and management regimes of preventive restore their functionality and dependability